Development of a smartphone virtual reality game to support the radiation therapy of children and adolescents in proton centers - Schenck, Leonardo; Bäumer, Christian; Ross, Björn; Schäfer, Gabriele; Stember, Nicole; Thomas, Heike; Stieglitz, Stefan; Timmermann, Beate (Frontiers in Pediatrics, 2023)
For most patients, cancer therapy with radiation is a new experience coming with many unknown challenges. This can be stressful, particularly for children and adolescents. With the aim of reducing this stress and anxiety, a virtual-reality (VR) game, which can be used by patients prior to treatment, was developed and evaluated in a proton therapy center. The specifications were derived from literature and from interviews with medical staff and patients. The gantry including the sound of its moving components and the sound of the interlock and safety system were identified as the main features relevant for preparation of a radiation course. Potential implementation difficulties were identified in a literature study and regarded in the design. Within the VR game, patients could interact with modeled equipment of the treatment room and hear the reportedly stress-inducing sounds in a stress-free environment prior to the treatment. The VR game was evaluated in a second series of interviews with patients. This exploratory study demonstrated the specification, implementation and safe application of a VR game dedicated to young proton therapy patients. Initial anecdotal evidence suggested that the VR gaming experience was well received and found to be helpful when preparing young patients for radiation therapy.